2004
DOI: 10.2174/1568009043332998
|View full text |Cite
|
Sign up to set email alerts
|

Microfilament Actin Remodeling as a Potential Target for Cancer Drug Development

Abstract: Actin was first identified in non-muscle cells only about three decades ago, and at about the same time, it was found that actin filaments were disrupted in the malignant transformed cells. The actin network is a rather complex, yet important structural and functional system of all eukaryotic cells. Actin filaments provide the basic infrastructure for maintaining cell morphology and functions such as adhesion, motility, exocytosis, endocytosis, and cell division. Growing evidence from this laboratory and other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
140
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 173 publications
(151 citation statements)
references
References 0 publications
7
140
1
Order By: Relevance
“…41 Previous studies have demonstrated that cancer cells are able to invade in 3D after treatment with a matrix metalloproteinase inhibitor cocktail, whilst showing the typical features of amoeboid invasiveness during migration; this indicates that blocking extracellular matrix proteolysis promotes mesenchymal-amoeboid transitions. 36,42 Inhibition of the ATPase activity of actin and myosin could reduce cell motility, 43 but targeting such fundamental cytoskeleton components might have severe side effects. A further attractive therapeutic strategy for GBM treatment has been shown to target cell surface growth factor receptors such as epidermal growth factor receptor, platelet-derived growth factor receptor and vascular endothelial growth factor receptor.…”
Section: Discussionmentioning
confidence: 99%
“…41 Previous studies have demonstrated that cancer cells are able to invade in 3D after treatment with a matrix metalloproteinase inhibitor cocktail, whilst showing the typical features of amoeboid invasiveness during migration; this indicates that blocking extracellular matrix proteolysis promotes mesenchymal-amoeboid transitions. 36,42 Inhibition of the ATPase activity of actin and myosin could reduce cell motility, 43 but targeting such fundamental cytoskeleton components might have severe side effects. A further attractive therapeutic strategy for GBM treatment has been shown to target cell surface growth factor receptors such as epidermal growth factor receptor, platelet-derived growth factor receptor and vascular endothelial growth factor receptor.…”
Section: Discussionmentioning
confidence: 99%
“…34 At a later stage, the tumor cells may regain the actin polymerization capability through the activation of Ras superfamily GTPase (Rac/Rho/CDC42) that causes re-distribution of actin filaments in a way favoring cellular movement and migration. 14 Green tea stimulates annexin-1 expression Q-Y Lu et al has been shown that the distribution of actin filaments, rather than the net actin polymerization, may be more important in determining cellular adhesion and motility, at least in epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Alterations of actin polymerization drive invasive morphological changes in malignant cells including modulation of adhesion complexes and, associated with them, microfilaments (Gimona, 2008). Actin remodelling could be the result of activation of oncogenic signalling pathways, or misexpression of some actin-binding proteins (Rao and Li, 2004). Wt1 was named as one of the proteins implicated in actin cytoskeletal changes in cancer cells (Jomgeow et al, 2006) and cultured podocytes (Viney et al, 2007).…”
Section: Gfp-hnrnpa1 T7-wt1+/+ Gfp-sf2mentioning
confidence: 99%